Phorbol-12-myristate-13-acetate is a potent enhancer of B cells with a granzyme B+ regulatory phenotype - Veh, Johanna; Mangold, Charlotte; Felsen, Anja; Ludwig, Carolin; Gerstner, Lisa; Reinhardt, Peter; Schrezenmeier, Hubert; Fabricius, Dorit; Jahrsdörfer, Bernd (Frontiers in Immunology, 2023)
The infusion of ex-vivo-generated regulatory B cells may represent a promising novel therapeutic approach for a variety of autoimmune and hyperinflammatory conditions including graft-versus-host disease. Previously, we developed a protocol for the generation of a novel population of regulatory B cells, which are characterized by secretion of enzymatically active granzyme B (GraB cells). This protocol uses recombinant interleukin 21 (IL-21) and goat-derived F(ab)'2 fragments against the human B cell receptor (anti-BCR).Generally, the use of xenogeneic material for the manufacturing of advanced therapy medicinal products should be avoided to prevent adverse immune reactions as well as potential transmission of so far unknown diseases. In the present work we demonstrated that phorbol-12-myristate-13-acetate (PMA/TPA), a phorbol ester with a particular analogy to the second messenger diacylglycerol (DAG), is a potent enhancer of IL-21-induced differentiation of pre-activated B cells into GraB cells. The percentage of GraB cells after stimulation of pre-activated B cells with IL-21 and PMA/TPA was not significantly lower compared to stimulation with IL-21 and anti-BCR. Given that PMA/TPA has already undergone encouraging clinical testing in patients with certain haematological diseases, our results suggest that PMA/TPA may be a safe and feasible alternative for ex-vivo manufacturing of GraB cells.Regulatory B cells (Bregs) represent a heterogeneous group of B cells capable of suppressing hyperinflammatory immune responses. The prominent role of Bregs in curbing pathological inflammatory responses has been associated with autoimmune diseases, graft rejections and allergies. A variety of anti-inflammatory cytokines, but also enzymes and cytotoxic molecules can play key roles for their function. Recently, a highly active population of Bregs characterized by expression of enzymatically-active granzyme B (GraB cells) came into clinical focus. However, so far no clinical trials with GraB cells and other Bregs were conducted, in part because their Good Manufacturing Practice (GMP)-compliant generation is highly challenging. Here we describe that the second messenger analogon phorbol-12myristate-13-acetate (PMA/TPA) potently enhances the generation of GraB cells, so that xenogeneic stimulants are no longer required for their generation. Our findings may represent an important step towards implementation of a Good Manufacturing Practice (GMP)compliant process for the generation of GraB cells for clinical use.